Integrasi Teknologi Digital dalam Pembelajaran Matematika untuk Mendukung Pendidikan Karakter Siswa Inklusif - Ahyani Mirah Liani (Journal of Mathematics, Statistics and Applications, 2026)
One aspect that is very necessary for every level of education in the world of education, especially in Indonesia, is character education and adaptation training to the development of the times because schools are one of the places where students form their personalities and also their abilities in facing society and the world of work. The purpose of this study is to further discuss the relationship between technological innovation and teacher professionalism in improving the quality of character education and literacy of changing times in the context of inclusive learning. The author uses primary studies as a reference, where the main findings show that professional teachers become facilitators and moral role models in integrating learning technology to shape the character of students. Digital literacy is considered capable of improving values such as honesty, responsibility, cooperation and problem-solving skills. In addition, education based on changing times must be integrated into the learning curriculum in order to improve students' adaptability in the development of the times through continuous learning and integrated activities. The results of this study emphasize the need to improve the ability to utilize technology for teachers and an active learning approach to achieve the goals of character development and saman literacy in inclusive education.